Lipase‐catalyzed modification of borage oil: Incorporation of capric and eicosapentaenoic acids to form structured lipids - Akoh, Casimir C.; Moussata, Charment O. (Journal of the American Oil Chemists' Society, 1998)
Abstract Two immobilized lipases, nonspecific SP435 from Candida antarctica and sn ‐1,3 specific IM60 from Rhizomucor miehei , were used as biocatalysts for the restructuring of borage oil ( Borago officinalis L.) to incorporate capric acid (10:0, medium‐chain fatty acid) and eicosapentaenoic acid (20:5n‐3) with the free fatty acids as acyl donors. Transesterification (acidolysis) reactions were carried out in hexane, and the products were analyzed by gas‐liquid chromatography. The fatty acid profiles of the modified borage oil were different from that of unmodified borage oil. Higher incorporation of 20:5n‐3 (10.2%) and 10:0 (26.3%) was obtained with IM60 lipase, compared to 8.8 and 15.5%, respectively, with SP435 lipase. However, SP435 lipase was able to incorporate both 10:0 and 20:5n‐3 fatty acids at the sn ‐2 position, but the IM60 lipase did not. Solvents with log P values between 3.5 and 4.5 supported the acidolysis reaction better than those with log P values between −0.33 and 3.0.